1995
DOI: 10.1007/bf00588010
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance tomographic angiography: diagnostic value in trigeminal neuralgia

Abstract: A combination of MRI, MR angiography and MR tomographic angiography (MRTA) was used to study the relationship of the root exit zone of the trigeminal nerve to surrounding vascular structures in seven patients with trigeminal neuralgia (TN) and ten patients with no evidence at a lesion in this region. MRTA is the technique for showing the relationship between vessels, cranial nerves and brain stem. MRTA clearly demonstrated the presence of a vessel at the root exit zone of the trigeminal nerve in all patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…There is great controversy about the imaging of neurovascular relationships at the surface of the brainstem, and the studies presented so far result in divergent conclusions, especially for the detection of neurovascular compression. 3,5,7,8,19,22,26,[31][32][33]37,45 This controversy resembles the discussion when Jannetta 21 introduced his concept of neurovascular compression as the cause of hyperactive cranial nerve dysfunction syndromes. It was difficult for Jannetta and other advocates of this hypothesis to convince the skeptics: 1 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There is great controversy about the imaging of neurovascular relationships at the surface of the brainstem, and the studies presented so far result in divergent conclusions, especially for the detection of neurovascular compression. 3,5,7,8,19,22,26,[31][32][33]37,45 This controversy resembles the discussion when Jannetta 21 introduced his concept of neurovascular compression as the cause of hyperactive cranial nerve dysfunction syndromes. It was difficult for Jannetta and other advocates of this hypothesis to convince the skeptics: 1 .…”
Section: Discussionmentioning
confidence: 96%
“…The majority of the studies conclude that MR imaging can be used to detect neurovascular compression in the classic compression syndromes like trigeminal neuralgia or hemifacial spasm. [3][4][5]7,25,44,45 Intraoperative photomicrographs and video documentation served as the basis for verifying the 3D visualization results. This comparison showed that our method is in fact able to demonstrate the relationships correctly (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,10 In classic TN, the superior cerebellar artery or one of its branches, the anterior inferior cerebellar artery, the PICA, or the basilar artery, usually compresses the root entry zone. 6,29,30 Rarely, the conflicting vessel is a petrous vein, a saccular aneurysm, a persistent trigeminal artery, or an AVM. 31,32 Recently, it has been shown that the size of the cerebellopontine cistern, as measured with MR imaging, may play a role in favoring a neurovascular conflict, because a significantly smaller volume of the cistern was found in patients who had TN on the affected side.…”
Section: Vascular Lesionsmentioning
confidence: 98%
“…Neurotransmitter 9 Substanz P 9 Somatostatin Die Atiologie der Trigeminusneuralgie ist nach wie v0r unbekannt. Zahlreiche neuroradiologische [44], neuroanatomische [45,20] und neurochirurgische Befunde [31,39] legen eine periphere Genese des Schmerzes bei der Trigeminusneuralgie nahe. MOgliche Ursachen einer chronischen mechanischen Irritation der Trigeminuswurzel bestehen z.B.…”
Section: Schliisselworterunclassified